Adat “Angkan-Angkanan” Suku Komering sebagai Pintu Masuk Hamba Lintas Budaya - Darmanto D (Sekolah Tinggi Theologia Nazarene Indonesia, 2016)
The world of ministry in Indonesia is very diverse with many of tribes, cultures and languages​​. Often minstersare faced with many obstacles, one being cultural barriers or customs that often clash with the demands of the Gospel. There are three principles in addressing the culture or customs that we should remember, namely: there are culture values and customs that can be retained, there are culture values and customs that need to be modified and aligned with biblical teaching, but there is also a cultural values and customs that must be rejected as contrary to the truth of the gospel . Among the Komering people group, for example, there is an existing tribal custom called